Pre-induction Jerky limb movements on operation table – Is it transient ischemic attack (Indian Journal of Case Reports, 2022)
Transient ischemic attack (TIA) is a diagnostic challenge for all physicians due to the temporariness of symptoms and the absence of any definitive diagnostic test. There is a very high risk of TIA being followed by an ischemic stroke, hence require urgent investigation and preventive strategies. At the same time, it is also important to distinguish TIA from other close differentials, to avoid wrong diagnoses leading to harmful, misdirected medical management. In this report, we will discuss the case of a middle-aged male patient with stable pre-operative vitals who was posted for total parotidectomy and suddenly developed jerky movement of the upper limb and transient aphasia on the operation theater table along with raised blood pressure. This is a very rare presentation of TIA that needs to be differentiated from other close differentials as this form is mostly associated with severe carotid occlusive disease and, hence, carries a high risk of stroke.